Rabop kānwikhr̨o phonkrathop singw̄ætl̨̄om kh̨̄ong Prathēt Thai (K̨̄ong Wikhr̨o Phonkrathop Singw̄ætl̨̄om, Samnakngān Nayōbāi læ Ph̄æn Singw̄ætl̨̄on, 1997)
Analysis on factors affecting environmental conditions of Thailand.